The Legal Certainty in the Application of Sanctions for the Abuse of Narcotics Class I Not Derived from Plants Based on the Principle of Justice (A Study of Decision Number: 528/Pid.Sus/2025/PN Tjk) - Jainah, Zainab Ompu; Ramadan, Suta; Ningrum, Intan Putri Yani Cahya; Anggara, Firga Fiksona (The Future of Education Journal, 2026)
Class I narcotics crimes that are not plants are serious crimes that have a wide impact on public health, security, and order, and threaten the future of the nation's generation. One of the important problems in handling narcotics crimes is ensuring legal certainty in the application of criminal sanctions to perpetrators who commit acts without rights and against the law. The problems raised are: Legal Certainty in the Application of Sanctions Without Rights and Against the Law on Class I Narcotics Crimes that are not Plants Based on Decision Number 528 / Pid.Sus / PN Tjk. and What are the factors causing perpetrators to commit Class I narcotics Abuse based on the principle of justice. The research method uses a normative and empirical juridical approach. The normative juridical approach is taken through a literature study by examining relevant laws and regulations, doctrines, and legal literature. Meanwhile, the empirical approach is carried out by interviewing parties involved or directly understanding the case to obtain a factual picture regarding the application of the law in the field. The results of the study indicate that the application of criminal sanctions to the defendant in Decision Number 528/Pid.Sus/2025/PN Tjk has fulfilled the principle of legal certainty, especially regarding the fulfillment of the elements of "without rights and against the law" as regulated in Article 112 paragraph (1) of Law Number 35 of 2009 concerning Narcotics. However, there are still several inhibiting factors in the application of legal certainty, These include differences in legal interpretation, limited evidence, and the influence of non-juridical factors in the law enforcement process. Factors causing class I drug abuse include environmental factors, drug dependence, and family factors. The judge's considerations in the decision emphasized aspects of legal certainty and community protection, but did not fully reflect the principle of substantive justice that prioritizes a rehabilitative approach for drug abusers as victims of dependence. The imposition of prison sentences on class I drug users still raises debate regarding its suitability with the objectives of punishment and the spirit of rehabilitation mandated by law. The suggestion from this study is that the handling of class I drug abuse cases needs to prioritize substantive justice through the implementation of rehabilitation for pure abusers, supported by the active role of the community in prevention in order to create legal certainty and suppress drug distribution.